Heat Transfer and Pressure Drop Characteristics of Graphene Oxide/Water Nanofluid in a Circular Tube Fitted with Wire Coil Insert. Issue 2 (3rd March 2016) - Mirzaei, M.; Azimi, A.
Abstract : In this work, heat transfer and pressure drop characteristics of graphene oxide/water nanofluid flow through a circular tube having a wire coil insert were studied. The required graphene oxide was synthesized via the Hummer method and characterized using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (SRD), and scanning electron microscope (SEM) methods. Dispersing graphene oxide in the water, nanofluids with 0.02, 0.07, and 0.12% volume fraction were prepared. An experimental set-up was designed and made to investigate the heat transfer performance and pressure loss of nanofluids. All experiments were carried out in the constant heat flux at tube wall conditions. The volumetric flow rates of the nanofluid were adjusted at 6, 8, and 10 L/min. Thermal conductivity, specific heat, density, and viscosity as thermophysical properties of the nanofluid were calculated using graphene oxide and water properties at the average temperature via appropriate relations. These properties were applied to calculate the convective heat transfer coefficient, Nusselt number, and friction factors for each experiment. Finally, the constant and exponents of Duangthongsuk and Wongwises's correlations for Nusselt number and friction factor were corrected by experimental results. The achieved experimental data have shown good agreement with those predicted. The results have shown that 0.12 vol% of graphene oxide in the water can enhance convective heat transfer coefficient by about 77%. As a result, it can be concluded that the graphene oxide/water can be used in the heat transfer devices to achieve more efficiency.